Hubungan Iklan Lemonilo X NCT Dream dengan Minat Beli Konsumen - Indryana Puspita Winaya; Satya Indra Karsa (Bandung Conference Series: Communication Management, 2022)
Abstract. Abstract. Advertising is a medium or means commonly used to market a company's product in order to be known by the public. Social media itself is one of the ways used to promote a product in this day and age. Instagram is one of the platforms chosen and considered practical for presenting product advertisements. Lemonilo, as a company that is famous for its healthy instant noodle products, collaborated by inviting NCT Dream boyband from South Korea as their advertisement star and marketing it on Instagram. The purpose of this study was to determine the relationship between attitudes, memory, frequency of clicks on the Lemonilo x NCT Dream Instagram ad with the attention, interests, desires and actions of followers to buy Lemonilo x NCT Dream advertising products. The theoretical basis used is the S-O-R Theory (Stimulus, Organism, Response) with the research methodology used is correlational quantitative. Research techniques through questionnaires, literature, and observation. The object of this research is followers on the Instagram account @lemonilo. The results obtained are Ho is rejected where there is a relationship between attitude, attractiveness, frequency of clicks on the Lemonilo x NCT Dream Instagram ad with the attention, interest, desire and action of followers to buy Lemonilo x NCT Dream advertising products. Abstrak. Iklan adalah sebuah media atau sarana yang biasa digunakan untuk memasarkan suatu produk perusahaan guna untuk dikenal oleh khalayak. Media sosial sendiri menjadi salah satu cara yang digunakan untuk mempromosikan suatu produk di zaman sekarang ini. Instagram menjadi salah satu platform yang dipilih dan dianggap praktis untuk menyajikan iklan produk. Lemonilo sebagai suatu perusahaan yang terkenal dengan produk mie instan sehatnya melalukan kerjasama dengan mengajak NCT Dream boyband yang berasal dari negara Korea Selatan sebagai bintang iklan mereka dan memasarkannya di Instagram. Tujuan dari penelitian ini ialah guna mengetahui hubungan antara sikap, daya ingat, frekuensi klik iklan Instagram Lemonilo x NCT Dream dengan perhatian, minat, keinginan dan tindakan followers untuk membeli produk iklan Lemonilo x NCT Dream. Landasan teori yang digunakan adalah Teori S-O-R (Stimulus, Organism, Respon) dengan metodologi penelitian yang digunakan adalah kuantitatif korelasional. Teknik penelitian melalui kuesioner, kepustakaan, dan observasi. Objek pada penelitian ini yakni followers pada akun Instagram @lemonilo. Hasil penelitian yang didapatkan adalah Ho ditolak dimana terdapat adanya hubungan antara sikap, daya tarik, frekuensi klik iklan Instagram Lemonilo x NCT Dream dengan dengan perhatian, minat, keinginan dan tindakan followers untuk membeli produk iklan Lemonilo x NCT Dream.